Description of the last larval instar and pupa of Aspisoma fenestrata Blanchard, 1839 (Coleoptera: Lampyridae) with brief notes on its biology - Archangelsky, Miguel (2004)
The last instar larva and pupa of Aspisoma fenestrata are described and figured for the first time. Notes for comparison with two other unidentified Aspisoma larvae are provided, as well as brief notes on the biology of A. fenestrata. Comparison of Aspisoma larvae with other known Cratomorphini larvae places Aspisoma closer to Pyractomena than to Cratomorphus.